CLINICAL-EPIDEMIOLOGICAL PROFILE OF COVID 19-RELATED CARE AT A REFERENCE HOSPITAL IN ANÁPOLIS-GO IN 2020 - Oliveira, Gabriela Luiza da Silva; Alvares , Laize Evelyn Magalhães de Brito; Dias , Pollyana Ferreira; de Jesus, Rafael Neves; Pinto, Emerith Mayra Hungria (CIPEEX, 2022)
THE PANDEMIC CAUSED BY THE DISEASE CORONAVIRUS 19 (CORONAVIRUS DISEASE 2019, COVID-19) KILLED COUNTLESS PEOPLE IN 2020 AND ARRIVED IN BRAZIL IN MID-FEBRUARY OF THE SAME YEAR, SPREADING QUICKLY, IN VIEW OF ITSFACILITATED FORM OF TRANSMISSION BY DROPLETS OFSALIVA, COUGHING, SNEEZING AND CONTAMINATED SURFACES. SEVERAL STUDIES HAVE INDICATED THAT MALE PEOPLE OVER 60 YEARS OF AGE WITH COMORBIDITIES SUCH AS DIABETES MELLITUS, CHRONIC KIDNEY DISEASE, CARDIOVASCULAR DISEASE AND/OR CHRONIC LUNG DISEASES HAD HIGHER RATES OF PROGRESSION TO RESPIRATORY SYNDROME (SARS) AND GREATER VULNERABILITY TO DEATH. THUS, WITH THE OBJECTIVE OF DESCRIBING THE CLINICAL-EPIDEMIOLOGICAL PROFILE OF SUSPECTED AND CONFIRMED PATIENTS FOR COVID-19 IN A HOSPITAL IN ANÁPOLIS/GOIS, MEDICAL RECORDS OF PATIENTS SUSPECTED AND CONFIRMED FOR COVID-19 IN THE PERIOD FROM MARCH TO DECEMBER 2020 WERE ANALYZED IN RELATION TO CLINICAL-EPIDEMIOLOGICAL VARIABLES. A TOTAL OF 1170 PATIENTS WERE INCLUDED IN THIS STUDY, WITH 54.8% OF PATIENTS ADMITTED WITH SYMPTOMS FOR COVID-19 WERE WOMEN, WITH 46.9% AGED BETWEEN 30 AND 59 YEARS. IN ADDITION, IT WAS NOTED THAT 11.5% OF THESE PATIENTS HAD COMORBIDITIES. FURTHERMORE, THE DATA REVEALED THAT 82.2% OF THE LABORATORY-CONFIRMED PATIENTS WHO DIED HAD COMORBIDITIES, MOST OF THEM MEN (57%), AND OF THE TOTAL 68.5% HAD TWO OR MORE COMORBIDITIES, WITH CARDIOVASCULAR ORIGIN BEING THE MOST FREQUENT REACHING 77.5% OF THE SAMPLE. THUS, IT WAS CONCLUDED THAT THE CLINICAL-EPIDEMIOLOGICAL PROFILE OF SUSPECTED AND CONFIRMED PATIENTS FOR COVID-19 IN THIS RESEARCH WAS CHARACTERIZED BY THE MAJORITY OF FEMALE PATIENTS BETWEEN 30 AND 49 YEARS OF AGE, ALTHOUGH MOST CONFIRMED CASES AND DEATHS OCCURRED IN MEN WITH MORE THAN 60 YEARS. MOST CONFIRMED PATIENTS HAD TWO OR MORE COMORBIDITIES, MOST OF THEM OF CARDIOVASCULAR ORIGIN, FOLLOWED BY METABOLIC SYNDROMES, LUNG DISEASES AND OTHERS.